Mythologization of the Balkans in Postmodern Period: Bosnia and Herzegovina between Desire and Reality - Mujagić, Nermina; Bakić, Sarina (Technium Social Sciences Journal, 2022)
In this article, authors attempt to provoke the need of renewed understanding and researching related to the mythologization of the Balkans in Postmodern period. In the midpoint of this article is postmodern critic of international experts for legitimacy in ‘new state democracy’ (for example Bosnia and Herzegovina). Authors will try to make distinction between what is reality on the ground and what is the desirable model of Bosnia and Herzegovina for Europe. Regardless of various processes that are ongoing in Bosnia and Herzegovina, it is not possible to move away from mythological narratives and concepts